Type 3 secretion system effector genotype and secretion phenotype of longitudinally collected Pseudomonas aeruginosa isolates from young children diagnosed with cystic fibrosis following newborn screening. (13th February 2012) - Hu, H.; Harmer, C.; Anuj, S.; Wainwright, C. E.; Manos, J.; Cheney, J.; Harbour, C.; Zablotska, I.; Turnbull, L.; Whitchurch, C. B.; Grimwood, K.; Rose, B.; et al.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect 2013; 19: 266–272 Abstract Studies of the type 3 secretion system (T3SS) in Pseudomonas aeruginosa isolates from chronically infected older children and adults with cystic fibrosis (CF) show a predominantly exoS+/exoU− (exoS+) genotype and loss of T3SS effector secretion over time. Relatively little is known about the role of the T3SS in the pathogenesis of early P. aeruginosa infection in the CF airway. In this longitudinal study, 168 P. aeruginosa isolates from 58 children diagnosed with CF following newborn screening and 47 isolates from homes of families with or without children with CF were genotyped by pulsed‐field gel electrophoresis (PFGE) and T3SS genotype and phenotype determined using multiplex PCR and western blotting. Associations were sought between T3SS data and clinical variables and comparisons made between T3SS data of clinical and environmental PFGE genotypes. Seventy‐seven of the 92 clinical strains were exoS+ (71% secretors (ExoS+)) and 15 were exoU+ (93% secretors (ExoU+)). Initial exoS+ strains were five times more likely to secrete ExoS than subsequent exoS+ strains at first isolation. The proportion of ExoS+ strains declined with increasing age at acquisition. No associations were found between T3SS characteristics and gender, site of isolation, exacerbation, a persistent strain or pulmonary outcomes. Fourteen of the 23 environmental strains were exoS+ (79% ExoS+) and nine were exoU+ (33% ExoU+). The exoU+ environmental strains were significantly less likely to secrete ExoU than clinical strains. This study provides new insight into the T3SS characteristics of P. aeruginosa isolated from the CF airway early in life.